New combinations and names for continental American Calyptranthes (Myrtaceae: Myrcia s.l.) - Lourenço, Ana Raquel Lima; Parra-O., Carlos; Sánchez-Chávez, Erandi; Lucas, Eve (Phytotaxa, 2018)
129 currently accepted names (all continental American Calyptranthes, but six also occurring in the Caribbean) are here transferred to Myrcia, a required step towards a new classification of the Myrcia s.l. group supported by molecular phylogenetic and morphological studies. Geographical distribution is indicated for each species.